Mulheres de Hallyu: a representação feminina no cinema sul-coreano - Monteiro, Ana Maria Antunes (Universidade Federal de São Carlos, 2023)
Based on the analysis of the feature films A Girl at My Door (2014) by Jung July, Missing (2016) by Lee Eon Hee and Kim Ji Young, Born 1982 (2019), this study focuses on observing the feminist discourse of South Korean female directors from three perspectives: sexuality, motherhood, and work. We established relationships between the theory of melodrama and han (恨); using feminist film theory, we analyzed the Confucian concepts of the three obediences (三從之道); the seven sins (七去之惡) and the wise mother, good wife (賢母良 妻) present in the selected works. We displayed in an introductory way the history of cinema in the Korean peninsula in parallel with the main political events of the 20th century; and the participation of women in the development of East Asian cinematographic language. For example, Park Nam Ok portrayed in The Widow (1955) the difficulties of a widow raising her daughter during the war. Like her, other female directors have also used cinema to show the gender inequalities faced in South Korea. In this thesis, we sought to answer the current challenges faced by female audiovisual directors.

본 연구는 정주리 감독의 도희야(2014), 이언희 감독의 미씽: 사라진 여자(2016), 김도영 감독의 82년생 김지영(2019)을 분석하여, 한국 여성 감독들의 페미니즘 담론을 성(性), 모성(母性), 그리고 노동(勞動)의 세 가지 관점에서 관찰하는 데 중점을 두고 있다. 멜로드라마 이론과 '한(恨)'의 개념 간의 관계를 설정하였고, 페미니즘 영화 이론을 바탕으로, 선택된 작품들에 내재된 유교적 개념인 삼종지도(三從之道), 칠거지악(七去 之惡), 현모양처(賢母良妻)를 분석하였다. 우리는 20세기 주요 정치적 사건들과 병행하여 한반도의 영화사를 서론에서 간략히 설명하고, 동아시아 영화 언어 발전에 있어서 여성의 참여를 다루었다. 박남옥 감독은 자신의 첫 작품 미망인(1955)에서 전쟁 중 딸을 키우는 한 과부의 어려움을 묘사하였다. 그녀와 마찬가지로, 다른 여성 감독들도 영화를 통해 한국에서 직면한 성차별을 드러내고자 하였다. 본 논문에서는 현대 한국 여성 감독들이 직면한 도전 과제에 대한 해답을 모색하였다.

Sur le base de l'analyse des films de long-métrage A Girl at My Door (2014) de Jung July, Missing (2016) de Lee Eon Hee et Kim Ji Young, Born 1982 (2019), ce travail s'intéresse au discours féministe des réalisatrices sud-coréennes sous trois angles: la sexualité, la maternité et le travail. Nous établissons des relations entre la théorie du mélodrame et Han (恨) et, au regard de la théorie féministe du cinéma, nous analysons les concepts confucéens des trois obéissances (三從之道), des sept péchés (七去之惡) et de la mère sage, bonne épouse (賢母 良妻) présents dans les œuvres sélectionnées. À ce propos, nous présentons, en introduction, l'histoire du cinéma dans la péninsule coréenne en parallèle avec les principaux événements politiques du 20e siècle, et la participation des femmes au développement du langage cinématographique est-asiatique. Par exemple, Park Nam Ok qui, dans son premier film The Widow (1955), a présenté les difficultés d'une veuve élevant sa fille pendant la guerre. Comme elle, d'autres réalisatrices ont utilisé le cinéma pour montrer les inégalités entre les sexes en Corée du Sud. Dans cet article, nous cherchons à répondre aux défis actuels auxquels sont confrontées par les réalisatrices audiovisuelles.
Women of Hallyu: female representation in south korean cinema
Keywords: Cinema sul-coreano; Cinema feminista; Hallyu; Análise fílmica; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA